PENGARUH METODE PEMBELAJARAN VALUE CLARIFICATION TECHNIQUE (VCT) TERHADAP SIKAP DISIPLIN PESERTA DIDIK DALAM PEMBELAJARAN PPKn KELAS IV SD NEGERI KALIASIN III - Putri Awaliah; Damanhuri Damanhuri; Ikman Nurahman (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This research aimed to determine the influence of Value Clarification Technique (VCT) on the students’ discipline in learning civic at grade IV. The method of this research was Quasi Experiment conducted at grade IV. This research used two classes, namely the experimental class and the control class. Class IV A, as the experimental class, consisted of 30 students and Class IV B, as the control class, also consisted of 30 students. Based on the research conducted, it was revealed that there was a significant influence of implementation of of Value Clarification Technique (VCT) on the students’ discipline in civic subject. The results of the discipline questionnaire for VCT model obtained a score of 84.63. Whereas, the results of the discipline questionnaire for the lecture method was 65.23. Moreover, based on the results of t test in which 0.000 <0.05, it was concluded that there was an effect of Value Clarification Technique (VCT) method on the students’ discipline and the use of Value Clarification Technique (VCT) method was better than the lecture method.